HUBUNGAN HYGIENE SANITASI DENGAN KEBERADAAN BAKTERI ESCHERICHIA COLI PADA MINUMAN ES CAPPUCINO DI KECAMATAN PLAJU KOTA PALEMBANG: HUBUNGAN HYGIENE SANITASI DENGAN KEBERADAAN BAKTERI ESCHERICHIA COLI PADA MINUMAN ES CAPPUCINO DI KECAMATAN PLAJU KOTA PALEMBANG - Rahmi Garmini; Nurafni Maftukhah (IKesT Muhammadiyah Palembang, 2024)
Background: Cappuccino iced drink is one of the most popular drinks people are interestedin, if in the management of drinks it is not hygiene and sanitary may result in the presence of ingredients in food and drink that can cause health problems for consumers. Purpose: The purpose of this research to analyze the relationship of sanitary hygiene with the presence of bacteria esccherichia coli on a cappuccino iced drink. Method: Using a Cross Sectional Research Design. Research Sample were 30 person. Types of Qualitatif Results: Based on statistical tests with the Chi Square test, the p value is ≥ 0,05 (0,201) so That Ha is rejected, meaning there is no relationship between Knowledge and Personal Hygiene. The results of statistical tests with the chi square test show a p value of ≤ 0,001 ) p value ≤ 0,05) Ha is accepted, meaning there is a relationship with Attitudes towards Personal Hygiene. The results of the Chi Square Statistical test showed that the p value was ≥ 0,05, namely 0,113, so Ha was rejected, meaning there was no relationship between behavior and Personal Hygiene. Conclusion: It shows that there is a relationship between personal hygiene of handlers, there is a relationship between equipment sanitation hygiene, there is a relationship between sanitation hygiene at places where drinks are sold, and there is a relationship between ice cappuccino vending facilities and the presence of Escherichia coli bacteria by showing a value of (p<0.05), there is no relationship between raw materials. with the presence of Escherichia Coli bacteria in the iced cappuccino drink showing a value of (p>0.05), the OR value = 8.333, meaning that Hygiene Sanitation of Raw Materials has an 8.33 times chance of the presence of Escherichia Coli bacteria, while from laboratory results it is 6.7% of all iced cappuccino drink samples were positive for Escherichia Coli and 9.33% of iced cappuccino drink samples were negative for Escherichia Coli in accordance with RI Minister of Health Regulation No. 1096/MENKES/PER/IV/2011 concerning Health Requirements for Hand-Wiped Cutlery, Food Ingredients, and Food (Catering Services) with requirements for pathogenic germs